Feasibility assessment of using Wavestar energy converter in a grid-connected hybrid renewable energy system (a case study) - Mohammad Hossein Jahangir; Fatemeh Salmanpour; Erfan Sadeghitabar (Energy Conversion and Management: X)
Renewable energies, as a sustainable alternative to fossil fuels, confront a twofold challenge characterized by intermittency and the imperative to enhance reliability. Hybrid energy systems (HES) emerge as a pragmatic solution with the potential to mitigate carbon emissions and foster self-sufficiency within local communities. This investigation primarily seeks to ascertain the optimal configuration of a HES integrated with Wavestar wave energy converter, considering economic, technical, and environmental factors, tailored to meet the electricity demands of two cities in Iran including Chabahar and Anzali alongside of the Caspian sea and Oman sea, respectively. For this purpose, HOMER software is used for modeling and optimization the energy systems. In both locations, the optimal system includes photovoltaic (PV), wind turbine (WT), Wavestar wave energy converter (WEC), diesel generator (DG), and batteries which results in cost of energy (COE) of 0.136 and 0.109 in Chabahar and Anzali, respectively. Sensitivity analysis reveals that wind speed significantly impacts COE and reliability, also grid electricity purchases play a vital role. Economic uncertainty highlights varying importance between capital costs for PV and WT in Anzali and Chabahar. Furthermore, this study delves into the limitations posed by the fuel dependency of diesel generators. Finally, by conducting a thorough assessment of solar energy potential by GIS software, the research identifies a favorable location for the establishment of a solar power plant, contributing to the overall feasibility of the proposed hybrid energy systems.